Peran Pendidikan Agama Kristen dalam Membangun Karakter Anak pada Usia 7-12 Tahun di Gereja Alfa Omega Uluklubuk - Yunita Selviana Halla; Harun Y. Natonis (Lembaga Yasin AlSys, 2026)
Christian Religious Education plays an important role in shaping children’s character, particularly among children aged 7–12 years, which is a developmental stage for moral and spiritual values. The church, as a religious institution, is responsible for instilling Christian values through Sunday school and spiritual guidance. However, technological developments, social environmental influences, and limited family support pose challenges to the process of children’s character formation. This study aimed to analyse the role of Christian Religious Education in building the character of children aged 7–12 years at Alfa Omega Church, Uluklubuk, Kupang. This study employed a qualitative approach using field research. Data were obtained through observations, interviews, and documentation involving Sunday school teachers, church administrators, parents, and children aged 7–12 years. The data were analysed through the stages of data reduction, data presentation, and conclusion drawing, while their validity was examined using source and technique triangulation. The results showed that Christian Religious Education played a role in building children’s character through Bible story-based learning, communal prayer, praise, educational games, and the exemplary conduct of Sunday school teachers. The character values instilled included discipline, responsibility, honesty, love, cooperation, and respect for parents and teachers. Successful character formation was supported by teacher involvement, church support, and parental participation, whereas inhibiting factors included the influence of social media, limited learning facilities, and differences in family backgrounds. This study confirms that Christian Religious Education contributes to the formation of children’s moral and spiritual character. The implications of this study indicate the need to strengthen cooperation among the church, family, and community to continuously optimize children’s character education.